Information-seeking barriers and strategies in maternity care: a framework analysis of nurses' goals, plans, and actions. (3rd July 2022) - Dalton, Elizabeth D.; Miller, Laura E.; Pjesivac, Ivanka; Eldredge, Scott A.
ABSTRACT: Background: There is limited understanding about informational barriers that nurses face when assessing obstetric patients and the strategies they use to obtain and elicit disclosure of potentially sensitive health information. Using framework analysis and goals-plans-actions theory, this study qualitatively explores the perspectives of nurses, nurse practitioners, and midwives on these processes and strategies. Methods: This study utilizes framework analysis to analyze in-depth interviews with 22 nurses working in the field of obstetric and intrapartum care. Results: Two overarching themes regarding barriers to disclosure and six themes regarding strategies to address these barriers emerged. Barriers included intentional self-concealment and unintentional omission of information. Strategies to overcome these barriers include education, rapport building, strategic questioning, creating a zone of privacy, seeking out information from other sources, and postnatal debriefing sessions. Conclusion: This study provides greater insight into the types of barriers that may prevent pregnant people from disclosing their health information, as well as communicative strategies on how to elicit sensitive health information. Nurses' responses highlight their reliance on patients, as well as on other sources of information when encountering patient reticence. Framework analysis points to four overarching strategic implications for communicative practices in health care settings: creating mutual understanding, creating rapport, creating privacy, and creating more empowered and informed patients.